2001
DOI: 10.1016/s1010-7940(01)00597-8
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal cancer in Denmark: a nationwide study

Abstract: Tracheal cancers were rare and adenoid cystic carcinomas not as frequent as generally believed. Surgery was rarely offered. A resectability rate of only 10% is not adequately explained by selection bias and indicates a nihilistic attitude based on ignorance about surgical treatment of tracheal cancers. A more dedicated and aggressive approach with centralized workup and radical treatment is strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
108
2
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 22 publications
11
108
2
11
Order By: Relevance
“…6 Similar proportions were found in epidemiologic studies from Denmark and Finland. 7,8 The discrepancy between reported ratios of surgical clinics and these epidemiologic studies may be partly based on patient selection. However, some authors suspected a lack of knowledge and a nihilistic attitude toward the treatment of tracheal malignancies.…”
mentioning
confidence: 99%
“…6 Similar proportions were found in epidemiologic studies from Denmark and Finland. 7,8 The discrepancy between reported ratios of surgical clinics and these epidemiologic studies may be partly based on patient selection. However, some authors suspected a lack of knowledge and a nihilistic attitude toward the treatment of tracheal malignancies.…”
mentioning
confidence: 99%
“…Similarly, a more recent national study conducted in Denmark has reported a 52% 5-year survival rate in patients undergoing resection for adenoid cystic tumours compared to 33% in non surgically treated patients [33].…”
Section: Tracheal Resectionsmentioning
confidence: 91%
“…Overall periop-could be due to the limited numbers and the not systematically reported lymphadenectomy. Conversely, some authors [33,34] have shown a significant correlation between staging and survival in patients undergoing surgery.…”
Section: Tracheal Resectionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Yapılan epidemiyolojik çalışmalara göre hastaların %59'u erkektir ve bunlarında %73'ü sigara içmek-tedir. 3,4 Tanıları oldukça zordur ve rutin radyolojik tetkikler de çoğu zaman tanıda yetersiz kalır. Esas semptomları dispneyi takiben diğer üst hava yolu tıkanıklığı semptomlarıdır.…”
Section: Introductionunclassified